The Influence Of Business Strategy, Environmental Management, On Competitive Advantage Mediated By Innovation In Eco-Friendly Culinary Umkm In Yogyakarta City - Perdana Fiara Finda; Sabihaini; Heru Tri Sutiono (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
This study examines and analyzes the effect of Business Strategy, Environmental Management, on the Competitive Advantage of Eco-friendly Culinary MSMEs mediated by Innovation. The research method uses a quantitative approach with a sample of 122 respondents. The analysis tool uses Smart-PLS. The results in this study indicate that, Business Strategy has a positive and significant effect on Competitive Advantage; Environmental Management has a positive and significant effect on Competitive Advantage; Business Strategy has a positive and significant effect on Innovation; Environmental Management has a positive and significant effect on Innovation; Innovation has a positive and significant effect on Competitive Advantage. Then, Business Strategy has a positive and significant effect on Competitive Advantage mediated by Innovation; and Environmental Management has a positive and significant effect on Competitive Advantage mediated by Innovation. Based on the results of this study, it can be interpreted that the owners and managers of Culinary MSMEs have implemented business strategies that are more efficient and effective to make the latest products and can be enjoyed by consumers of Culinary MSMEs in Yogyakarta City. In addition, MSMEs have also implemented waste management generated from business activities and collaborated with local communities, then also implemented process innovation in an effort to prevent environmental pollution to increase competitive advantage.